Negative electrode material layer and electrochemical device and electronic equipment comprising same

By setting two active material layers in the negative electrode material layer of the sodium ion battery and controlling the crystal plane spacing of its micropore pore capacity and 002 plane, the problem of inability to take into account the energy density and cycle life of the sodium ion battery is solved, and the energy density and cycle life are synchronously improved, and a high capacity and long cycle sodium ion battery is obtained.

CN119905582AActive Publication Date: 2025-04-29ENVISION RUITAI DYNAMICS TECH (SHANGHAI) CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311414862.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29
Estimated Expiration
2043-10-27

AI Technical Summary

Technical Problem

The energy density and cycle life of existing sodium ion batteries cannot be taken into account, and how to simultaneously improve the energy density and cycle life of sodium ion batteries has become the focus of research.

Method used

By providing two active material layers in the negative electrode material layer of the electrochemical device, the micropore pore volume of the first active material layer and the second active material layer and the crystal plane spacing of the 002 plane are regulated to meet a specific proportional relationship to achieve a synchronous improvement of energy density and cycle life.

Benefits of technology

The energy density and cycle life of sodium ion batteries are synchronously improved, and a sodium ion battery with high capacity and long cycles is obtained. The energy density can reach 128.9Wh/kg and above, and the capacity retention rate of 1,000 cycles can be 85.8% and above.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004519316680000091
    Figure BDA0004519316680000091
  • Figure BDA0004519316680000101
    Figure BDA0004519316680000101
  • Figure BDA0004519316680000111
    Figure BDA0004519316680000111
Patent Text Reader

Abstract

The invention discloses a negative electrode material layer and an electrochemical device and electronic equipment comprising the negative electrode material layer. The negative electrode material layer comprises a first active material layer and a second active material layer arranged on the surface of the first active material layer; the first active material layer comprises a first active material; the first active material comprises amorphous carbon; the second active material layer comprises a second active material; the second active material comprises amorphous carbon; the amorphous carbon comprises hard carbon; the first active substance and the second active substance satisfy the following conditions: 1.05 < = A / B < = 2.00, and 0.90 < = C / D < = 0.98; wherein A represents the micropore volume of the first active material; b represents the micropore volume of the second active material; c represents the interplanar spacing of the 002 plane of the first active material; and D represents the interplanar spacing of the 002 plane of the second active material. When the negative electrode material layer provided by the invention is applied to an electrochemical device, synchronous improvement of energy density and cycle life is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention particularly relates to a negative electrode material layer and an electrochemical device and an electronic device containing the negative electrode material layer. Background Art

[0002] Sodium-ion batteries have the advantages of high energy density, good cycle life, excellent low-temperature performance, and low cost. They are gradually becoming an alternative to lithium-ion batteries and lead-acid batteries in the fields of energy storage, low-end power, and two-wheeled vehicles. The current mainstream solutions for the positive electrode of sodium-ion batteries are layered oxides and polyanions, and the mainstream solutions for the negative electrode are amorphous carbons such as soft carbon and hard carbon. In order to be more competitive, sodium-ion batteries still need to make breakthroughs in areas such as energy density and cycle life.

[0003] Currently, the most commonly used negative electrode material for sodium-ion batteries is hard carbon. The gram capacity of hard carbon materials is generally 280-320mA / g, the compaction density is 0.9-1.05g / cc, the energy density of the system with layered oxides is generally 115-140Wh / kg, and the cycle life is 2000-4000 cycles. However, compared with lithium iron phosphate batteries, there is still a certain gap in energy density and cycle life. How to simultaneously improve the energy density and cycle life of sodium-ion batteries has become the focus of current research in the industry. Summary of the invention

[0004] The present invention is mainly to overcome the defects of the prior art that the energy density and cycle life of the battery cannot be achieved at the same time, and provides a negative electrode material layer and an electrochemical device and an electronic device containing the same. When the negative electrode material layer provided in the present invention is used in an electrochemical device, the energy density and cycle life are improved simultaneously.

[0005] In a first aspect, the present invention provides a negative electrode material layer, which includes a first active material layer and a second active material layer disposed on the surface of the first active material layer;

[0006] The first active material layer comprises a first active material; the first active material comprises amorphous carbon;

[0007] The second active material layer comprises a second active material; the second active material comprises amorphous carbon;

[0008] The amorphous carbon comprises hard carbon;

[0009] The first active material and the second active material satisfy: 1.05≤A / B≤2.00, and 0.90≤C / D≤0.98;

[0010] Wherein A represents the micropore volume of the first active substance;

[0011] B represents the micropore volume of the second active material;

[0012] C represents the interplanar spacing of the 002 plane of the first active material;

[0013] D represents the interplanar spacing of the 002 plane of the second active material.

[0014] In a second aspect, the present invention provides an electrochemical device, which includes a negative electrode sheet, wherein the negative electrode sheet includes the negative electrode material layer and the negative electrode current collector as described above.

[0015] In a third aspect, the present invention provides an electronic device comprising the electrochemical device as described above.

[0016] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0017] The reagents and raw materials used in the present invention are commercially available.

[0018] The positive and progressive effects of the present invention are:

[0019] The present invention achieves a simultaneous improvement in the energy density and cycle life of a sodium ion battery by regulating the micropore volume of two layers of negative electrode active materials and the interplanar spacing of 002 planes. DETAILED DESCRIPTION

[0020] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0021] Negative electrode material layer

[0022] In the negative electrode material layer provided in the first aspect of the present invention, it includes a first active material layer and a second active material layer arranged on the surface of the first active material layer; the first active material layer contains a first active material; the first active material contains amorphous carbon; the second active material layer contains a second active material; the second active material contains amorphous carbon; the amorphous carbon contains hard carbon;

[0023] The first active material and the second active material satisfy: 1.05≤A / B≤2.00, and 0.90≤C / D≤0.98; wherein A represents the micropore volume of the first active material; B represents the micropore volume of the second active material; C represents the crystal plane spacing of the 002 plane of the first active material; and D represents the crystal plane spacing of the 002 plane of the second active material.

[0024] In the present invention, the micropore volume is the average micropore volume of the first active substance or the second active substance as a whole. The test method of the micropore volume is to take an appropriate amount of active substance and place it in a 9mm ball sample tube, degas at 300°C for 2h, and use nitrogen as the adsorbent (P / P0 range is 0-1, where a point is selected for every 0.002 in the range of 0-0.05, and a point is selected for every 0.05 in the range of 0.05-1) to measure the adsorption amount of the sample, and the pore volume below 2nm obtained by the non-local density functional theory (NLDFT) method is the micropore volume.

[0025] In the present invention, the interplanar spacing of the 002 plane refers to the interplanar spacing at the highest point of the characteristic peak height of the 002 plane in the XRD spectrum of the first active material or the second active material. In this specification, the XRD spectrum is a fitting spectrum of the XRD test results, and the "highest point" refers to the result displayed by the fitting data in the XRD spectrum. Individual noise will not affect the overall trend of the spectrum. The fitting and interpretation of the XRD spectrum are conventional methods in the art.

[0026] The test method of the interplanar spacing of the 002 surface is based on the record in the national standard GB / T 24533-2019. 0.15g of silicon powder and 0.35g of active material are weighed and fully ground in an agate mortar for 10 minutes, and then placed in a sample holder and flattened. The sample is scanned using an X-ray diffractometer at a condition of 25°-30° and a step size of 0.02°. The 002 peak of the active material is corrected using the silicon 111 peak to obtain the 002 peak 2θ value, and the interplanar spacing of the 002 surface is calculated using the Bragg equation.

[0027] In the present invention, in the amorphous carbon, the weight percentage of the hard carbon is greater than 90wt%, which refers to the weight percentage of the hard carbon in the whole amorphous carbon. Preferably, the amorphous carbon is hard carbon.

[0028] In some optional embodiments, the first active material is amorphous carbon, and the second active material is amorphous carbon.

[0029] In some optional embodiments, the first active substance and the second active substance may satisfy: 1.20≤A / B≤1.95.

[0030] In some specific embodiments, the A / B can be selected from 1.05, 1.09, 1.32, 1.62, 1.78, 1.91 or 2.00.

[0031] In some optional embodiments, the first active substance and the second active substance may satisfy: 0.91≤C / D≤0.96.

[0032] In some specific embodiments, the C / D can be selected from 0.90, 0.91, 0.92, 0.93, 0.95, or 0.98.

[0033] In some specific embodiments, the A / B=1.62, and the C / D=0.93.

[0034] In some specific embodiments, the A / B=1.78, and the C / D=0.91.

[0035] In some specific embodiments, the A / B=1.91, and the C / D=0.95.

[0036] In some specific embodiments, the A / B=1.05, and the C / D=0.95.

[0037] In some specific embodiments, the A / B=2.00, and the C / D=0.92.

[0038] In some specific embodiments, the A / B=1.09, and the C / D=0.90.

[0039] In some specific embodiments, the A / B=1.32, and the C / D=0.98.

[0040] In the present invention, the thickness ratio of the first active material layer to the second active material layer may be (1:3)-(3:1).

[0041] In some specific embodiments, the thickness ratio of the first active material layer to the second active material layer is 1:1, 1:3 or 3:1.

[0042] In the present invention, the thickness of the first active material layer may be 32 μm-96 μm, for example, 32 μm, 62 μm or 96 μm.

[0043] In the present invention, the thickness of the second active material layer may be 32 μm-96 μm, for example, 32 μm, 62 μm or 96 μm.

[0044] In the present invention, the weight ratio of the first active material to the second active material may be (1:3)-(3:1).

[0045] In some specific embodiments, the weight ratio of the first active substance to the second active substance is 1:1, 1:3 or 3:1.

[0046] In the present invention, in the first active material layer, the content of the first active material may be 90.0wt%-99.9wt%, where the percentage is the weight percentage of the first active material in the first active material layer.

[0047] In some specific embodiments, in the first active material layer, the content of the first active material may be 90.0 wt%, 98 wt% or 99.9 wt%, where the percentage is the weight percentage of the first active material in the first active material layer.

[0048] In the present invention, in the second active material layer, the content of the second active material is 90.0wt%-99.9wt%, where the percentage is the weight percentage of the first active material in the first active material layer.

[0049] In some specific embodiments, in the second active material layer, the content of the second active material is 90.0 wt%, 98 wt% or 99.9 wt%, where the percentage is the weight percentage of the first active material in the first active material layer.

[0050] In the present invention, the first active material layer and the second active material layer may each independently further include one or more of a conductive agent, a thickener and a binder.

[0051] The conductive agent is a conductive agent conventionally used in the art for preparing negative electrodes. Preferably, the conductive agent is one or more of conductive carbon black, carbon nanotubes and graphene, and more preferably conductive carbon black.

[0052] There is no particular limitation on the thickener. The addition of the thickener can increase the system viscosity of the components in the negative electrode active material layer. Generally, a sodium carboxymethyl cellulose (CMC) solution can be selected.

[0053] The binder may be a binder conventionally used in the art for preparing negative electrodes, for example, the following materials may be used as the binder: one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium carboxymethyl cellulose (CMC) and polyvinylidene fluoride (PVDF).

[0054] In some specific embodiments, the first active material layer includes: amorphous carbon, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber.

[0055] In some specific embodiments, the second active material layer includes: amorphous carbon, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber.

[0056] Electrochemical Devices

[0057] The electrochemical device described in the second aspect of the present invention comprises a negative electrode sheet; the negative electrode sheet comprises the negative electrode material layer and the negative electrode current collector as described above.

[0058] In some optional embodiments, the negative electrode sheet can be prepared by conventional methods in the art. For example, the following method can be used: after mixing the first active material (or the second active material), the conductive agent, the thickener and the binder in a certain weight ratio, adding a solvent and mixing evenly to obtain the first active material slurry or the second active material slurry; then firstly coating the first active material slurry evenly on the negative electrode current collector; then coating the second active material slurry on the first active material layer; and then drying, rolling, cutting and other processes to prepare the negative electrode sheet.

[0059] In some optional embodiments, in the negative electrode sheet, the negative electrode current collector is in direct contact with the first active material layer.

[0060] In the present invention, the negative electrode current collector may be a current collector conventionally used for the negative electrode in the art, and may be a common current collector or a composite current collector. The negative electrode current collector may use a material that does not cause chemical changes and has conductivity without restriction. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon or aluminum-cadmium alloy, or copper, stainless steel material or aluminum-cadmium alloy surface-treated with carbon, nickel, titanium or silver may be used. In addition, in order to enhance the adhesion of the negative electrode active material, micro-embossing may be formed on the surface of the negative electrode current collector. The negative electrode current collector may be used in various forms, such as a film, a sheet, a foil, a mesh or a porous body.

[0061] In some optional embodiments, the thickness of the negative electrode current collector may be about 16 μm.

[0062] In the present invention, the electrochemical device may be a sodium ion battery. The sodium ion battery comprises the negative electrode sheet, the positive electrode sheet, the separator and the electrolyte.

[0063] Positive electrode

[0064] In some embodiments, the positive electrode sheet is prepared by coating a positive electrode active material including a positive electrode active material on a positive electrode current collector, and a binder, a conductive agent, and a thickener may be further added as needed.

[0065] In some specific embodiments, the weight ratio of the positive electrode active material, conductive carbon black (Super P), carbon nanotubes (CNT), and binder polyvinylidene fluoride (PVDF) is 100:2:1:3.

[0066] The positive electrode active material may be a positive electrode active material conventionally used for the positive electrode of a sodium ion battery in the art. The positive electrode active material may be selected from layered oxides, Prussian blue compounds or polyanionic compounds. Further, the layered oxide may have a general formula of Na x[MFeMn]O2, M is at least one selected from Cu, Ni, Li, Mg, Al, Zn, Ti, Zr and Sn, and the range of x is x≤0.7. In a specific embodiment, the molecular formula of the positive electrode active material is NaNi 0.34 Fe 0.33 Mn 0.33 O2.

[0067] For the positive electrode current collector, materials that do not cause chemical changes and have high conductivity can be used without restriction. For example, stainless steel, aluminum, nickel, titanium or calcined carbon, or aluminum or stainless steel materials surface-treated with carbon, nickel, titanium, silver, etc. can be generally used. In order to enhance the adhesion of the positive electrode active material, micro-embossing can be formed on the surface of the positive electrode current collector. The positive electrode current collector can be used in various forms, such as a film, a sheet, a foil, a mesh or a porous body. Among them, the thickness of the positive electrode current collector can be about 16 μm.

[0068] In some embodiments, the positive electrode current collector is an aluminum foil with a thickness of 16 μm.

[0069] Diaphragm

[0070] In some embodiments, the separator can be a polypropylene separator or a polyethylene separator.

[0071] Wherein, the thickness of the isolation film may be about 9 μm.

[0072] In one embodiment, the separator is a 9 μm polyethylene separator coated on both sides with a ceramic coating having a thickness of 2 μm.

[0073] Electrolyte

[0074] In some embodiments, the electrolyte may be an electrolyte conventionally used for batteries in the art, generally including a non-aqueous solvent, a sodium salt, and an additive.

[0075] The non-aqueous solvent may be a conventional non-aqueous solvent in the art, preferably an ester solvent, more preferably a carbonate solvent. The carbonate solvent is preferably one or more of ethylene carbonate, dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC) and butylene carbonate (BC).

[0076] In some preferred embodiments, the non-aqueous solvent is a mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC) and propylene carbonate (PC) in a volume ratio of 1:1:1:1.

[0077] Among them, the additive is preferably one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl ethylene carbonate (VEC), diethyl sulfate (DTD), vinylene sulfate, 1,3-propane sultone (PS), allyl sultone and 1,4-butane sultone.

[0078] The sodium salt may be a conventional sodium salt in the art, such as NaPF6.

[0079] In the present invention, the preparation method of the sodium ion battery can be a conventional preparation method in the art, which can be a battery cell obtained by winding the positive electrode sheet, the negative electrode sheet and the isolation film, and then packaging them in a packaging shell and injecting the electrolyte; or it can be a battery cell obtained by stacking the negative electrode sheet, the isolation film, the positive electrode sheet and the isolation film in this order, and then packaging them in a packaging shell and injecting the electrolyte.

[0080] Electronic devices

[0081] The electronic device provided in the third aspect of the present invention comprises the electrochemical device as described above.

[0082] Exemplarily, the electronic device described in the present invention may be, but is not limited to, mobile devices (such as mobile phones, tablet computers, laptop computers, video recorders, portable printers / copiers, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems and backup power supplies, etc.

[0083] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0084] Examples 1-13 and Comparative Examples 1-5

[0085] Preparation of amorphous carbon

[0086] The amorphous carbon in Examples 1-13 and Comparative Examples 1-5 is hard carbon, and the preparation method thereof adopts the following steps:

[0087] Wash coconut shells three times with a mixed solution of water and ethanol (volume ratio of 1:1), then filter, dry and grind to obtain a coconut shell precursor; put the coconut shell precursor into a crucible, heat it to 200-600°C at 1-10°C / min under a nitrogen atmosphere, and keep it warm for 2-10 hours to obtain a carbon precursor; wash the carbon precursor three times with nitric acid / hydrochloric acid / hydrofluoric acid (volume ratio of 1:1:1), then wash it with deionized water for more than 5 times, and dry it to obtain a hard carbon precursor; heat the hard carbon precursor to 1000-1500°C at 1-10°C / min under a nitrogen atmosphere, and keep it warm for 2-10 hours; then ball mill it to the desired particle size to obtain amorphous carbon, which is hard carbon.

[0088] Among them, the micropore volume test method is: take an appropriate amount of amorphous carbon sample and place it in a 9mm ball sample tube, degas at 300℃ for 2h, and use nitrogen as the adsorbent (P / P0 range is 0-1, where 0-0.05 is a point selected every 0.002, and 0.05-1 is a point selected every 0.05) to determine the sample adsorption amount, and the pore volume below 2nm obtained by the non-local density functional theory (NLDFT) method is the micropore volume.

[0089] Among them, the test method for the interplanar spacing of the 002 plane is as follows: refer to the national standard GB / T 24533-2019, weigh 0.15g of silicon powder and 0.35g of amorphous carbon, grind them thoroughly in an agate mortar for 10 minutes, and put them into the sample holder and flatten them. The sample was scanned using an X-ray diffractometer with a condition of 25°-30° and a step size of 0.02°. The amorphous carbon 002 peak was corrected using the silicon 111 peak to obtain the 002 peak 2θ value, and the interplanar spacing of the 002 plane was calculated using the Bragg equation.

[0090] Preparation of negative electrode

[0091] The preparation methods of the negative electrode sheets in Examples 1-13 and Comparative Examples 1-5 adopt the following steps, and the specific parameter settings are shown in Table 1:

[0092] Preparation of the first active material layer: the first active material, conductive carbon black (Super P), thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber (SBR) are mixed uniformly in a weight ratio of 100:1:1:2, and appropriate deionized water is added, and stirred and dispersed uniformly to obtain a first active material slurry; the first active material slurry is uniformly coated on a 16 μm thick aluminum foil, and dried to obtain a first active material layer;

[0093] Preparation of the second active material layer: the second active material, conductive carbon black (Super P), thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber (SBR) are mixed uniformly in a weight ratio of 100:1:1:2, and appropriate deionized water is added, and stirred and dispersed uniformly to obtain a second active material slurry; the second active material slurry is uniformly coated on the surface of the first active material layer, and dried to obtain a second active material layer;

[0094] Among them, the first active material and the second active material are both amorphous carbon and meet the conditions recorded in Table 1; the thickness of the first active material layer and the second active material layer, the weight ratio of the first active material to the second active material, and the percentage of the active material in the active material layer are as recorded in Table 1.

[0095] The electrode sheet coated with the first active material layer and the second active material layer is rolled and cut into pieces to obtain a negative electrode sheet.

[0096] Table 1

[0097]

[0098]

[0099] Effect Example

[0100] Preparation of sodium ion batteries:

[0101] (1) Preparation of positive electrode

[0102] The positive electrode active material is a layered oxide with the molecular formula of NaNi 0.34 Fe 0.33 Mn 0.33 O2, the active material, conductive carbon black (Super P), carbon nanotubes (CNT), and binder polyvinylidene fluoride (PVDF) are mixed evenly according to a weight ratio of 100:2:1:3, and then N-methylpyrrolidone (NMP) is added and stirred to make it evenly dispersed to obtain a positive electrode slurry for a sodium ion battery; the positive electrode slurry is evenly coated on a 16μm thick aluminum foil, and after drying, rolling, and cutting, a positive electrode sheet is obtained.

[0103] (2) Preparation of electrolyte

[0104] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC) and propylene carbonate (PC) are uniformly mixed in a volume ratio of 1:1:1:1, and then an appropriate amount of NaPF6 is dissolved in the above mixed solution to prepare an electrolyte with a concentration of 1 mol / L.

[0105] (3) Preparation of diaphragm

[0106] The diaphragm is a 9μm polyethylene diaphragm coated on both sides with a 2μm thick ceramic coating.

[0107] (4) Preparation of sodium ion secondary batteries

[0108] The positive electrode sheet, separator, and electrolyte prepared in the above steps were assembled into a sodium ion battery with the negative electrode sheet prepared in Examples 1-13 and Comparative Examples 1-5, and the positive electrode sheet, separator, negative electrode sheet, and separator were alternately combined. After formation, a soft-pack battery with a capacity of 1Ah was obtained, and its effect was tested.

[0109] 1. Energy density (Wh / kg)

[0110] At a constant temperature of 25°C, charge to 4.0V at a constant current and voltage of 0.33C (constant voltage cutoff current is 0.05C), then discharge to 1.5V at a constant current of 0.33C. After 3 cycles, take the data after the last discharge as 0.33C energy, and weigh the cell weight with a balance. The ratio of 0.33C energy to cell weight is energy density. The test results are recorded in Table 2.

[0111] 2. Cycle life (%)

[0112] At 25°C, charge to 4.0V at 1C constant current and constant voltage (constant voltage cutoff current is 0.05C), and then discharge to 1.5V at 0.33C constant current. This is one cycle. Repeat the cycle 1000 times, and calculate the ratio of the discharge capacity of the 1000th cycle to the first cycle as the cycle life. The test results are recorded in Table 2.

[0113] Table 2

[0114]

[0115]

[0116] The negative electrode material layer provided by the present invention is applied to a sodium ion battery, which improves the energy density of the sodium ion battery and the cycle life of the sodium ion battery, thereby obtaining a sodium ion battery with both high capacity and long cycle life. The negative electrode material layer prepared in Examples 1-13 is applied to a sodium ion battery, and its energy density can reach 128.9Wh / kg or more, and the capacity retention rate after 1000 cycles can be 85.8% or more.

[0117] The difference between Comparative Examples 1 and 2 and the embodiment is that the value of the micropore volume A / B of the negative electrode active material is not within the scope of the present invention, and is too large or too small. Combined with the data in Table 2, it can be seen that its energy density and cycle life are both poor. This may be because the amorphous carbon is mainly a micropore filling sodium storage mechanism of amorphous carbon in the low voltage range close to 0V. The active material has a large micropore volume, which is conducive to micropore sodium storage and has a high gram capacity; therefore, to a certain extent, increasing the micropore volume of amorphous carbon is helpful to increase the sodium storage capacity of amorphous carbon. However, excessively increasing the micropore volume will reduce the compaction density of amorphous carbon, and will lead to more side reactions, reducing energy density and cycle life. Therefore, A / B must be within a reasonable range to take into account both energy density and cycle life.

[0118] The difference between Comparative Examples 3 and 4 and the embodiment is that the interplanar spacing C / D of the 002 plane of the negative electrode active material is not within the scope of the present invention. If it is too large or too small, its energy density and cycle life are both poor; this may be because the interplanar spacing of the 002 plane of amorphous carbon is related to the sodium ion diffusion resistance. A large interplanar spacing means a small sodium ion transmission resistance, which is beneficial to sodium ion transmission, and the energy density and cycle life will be improved; but excessively increasing the interlayer spacing will reduce the compaction density of amorphous carbon, reduce the structural stability, and lead to a reduction in energy density and cycle life. Therefore, C / D must be within a reasonable range to take into account both energy density and cycle life.

[0119] A / B and C / D in Comparative Example 5 are not within the scope of the present invention, and their cycle life and energy density are the worst. This is because the micropore volume of the first active material is smaller than that of the second active material, which is not conducive to micropore sodium storage; the interplanar spacing of the first active material is larger than that of the second active material, which is not conducive to sodium ion transmission, and therefore, their cycle life and energy density are the worst.

[0120] It can be seen from Examples 1-7 that when the first active material and the second active material satisfy: 1.05≤A / B≤2.00, and 0.90≤C / D≤0.98, the prepared sodium ion battery has good energy density and cycle life; especially when 1.20≤A / B≤1.95 or 0.91≤C / D≤0.96 is satisfied, the energy density and cycle life are higher. It is the present invention that obtains a sodium ion battery with both high capacity and long cycle by adjusting and optimizing the micropore volume of the two active material layers and the crystal plane spacing ratio of the 002 plane.

[0121] It can be seen from Examples 1, 8 and 9 that the thickness ratio and weight ratio of the first active material layer and the second active material layer also have a certain influence on the energy density and cycle life of the prepared sodium ion battery; this may be because the two layers of active materials have different interlayer spacings, and different interlayer spacings will affect the sodium ion transmission, and their thickness ratio or weight ratio will affect the sodium ion transmission path. Therefore, within a certain thickness ratio range, it has a better transmission effect, thereby having a better energy density and cycle life.

[0122] It can be seen from Examples 1 and 10-13 that when A / B and C / D are the same and within the scope of the present invention, the weight ratio of active materials in each active material layer will also affect the effect of the sodium ion battery, and the weight ratio will have a better effect within a suitable range. This may be because if the proportion of amorphous carbon is large, the electrode adhesion and conductivity are poor, affecting the sodium embedding ability and electrode stability, thereby affecting the cycle life and energy density; if the proportion is small, there is not enough micropore sodium storage, which will also affect the energy density and cycle life.

[0123] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A negative electrode material layer, characterized in that: It includes a first active material layer and a second active material layer arranged on the surface of the first active material layer; The first active material layer comprises a first active material; the first active material comprises amorphous carbon; The second active material layer comprises a second active material; the second active material comprises amorphous carbon; The amorphous carbon comprises hard carbon; The first active material and the second active material satisfy: 1.05≤A / B≤2.00, and 0.90≤C / D≤0.98; Wherein A represents the micropore volume of the first active substance; B represents the micropore volume of the second active material; C represents the interplanar spacing of the 002 plane of the first active material; D represents the interplanar spacing of the 002 plane of the second active material.

2. The negative electrode material layer according to claim 1, characterized in that The first active material and the second active material satisfy: 1.20≤A / B≤1.

95.

3. The negative electrode material layer according to claim 1, characterized in that The first active material and the second active material satisfy: 0.91≤C / D≤0.

96.

4. The negative electrode material layer according to claim 1, characterized in that The thickness ratio of the first active material layer to the second active material layer is (1:3)-(3:1).

5. The negative electrode material layer according to claim 1, characterized in that: The weight ratio of the first active material to the second active material is (1:3)-(3:1).

6. The negative electrode material layer according to claim 1, characterized in that: In the first active material layer, the content of the first active material is 90.0wt%-99.9wt%, where the percentage is the weight percentage of the first active material in the first active material layer.

7. The negative electrode material layer according to claim 1, characterized in that: In the second active material layer, the content of the second active material is 90.0wt%-99.9wt%, where the percentage is the weight percentage of the second active material in the second active material layer.

8. An electrochemical device, characterized in that: It comprises a negative electrode sheet; the negative electrode sheet comprises the negative electrode material layer as described in any one of claims 1 to 7 and a negative electrode current collector.

9. The electrochemical device according to claim 8, characterized in that The electrochemical device is a sodium ion battery.

10. An electronic device, characterized in that: It comprises the electrochemical device as claimed in claim 9.

Citation Information

Patent Citations

  • Anode active material and preparation method therefor

    CN109983605A

  • Hard carbon negative electrode material, negative electrode plate and battery

    CN115911368A

  • Hard carbon material, pole piece and electrochemical device

    CN116504971A

  • Negative active material and preparation method thereof, negative pole piece and secondary battery

    CN116885173A

  • Negative pole piece, secondary battery and apparatus thereof

    WO2020177623A1